2020
DOI: 10.21037/apm-19-367
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of type 2 diabetes mellitus on outcomes after one-lung ventilation during thoracic surgery: a retrospective cohort study

Abstract: Background: The preoperative presence of diabetes mellitus (DM) has been recently demonstrated to be a risk factor for adverse events after thoracic surgery. However, the specific effects of presence of DM preoperatively on thoracic surgery is not known. This study aimed to investigate the association between preoperative DM and clinical outcomes and the short-term survival rates after thoracic surgery.Methods: In this retrospective, observational, and matched-pair analysis study, patients receiving thoracic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Under the direct vision of a high-definition television imaging system, the operation system is inserted into the chest through chest wall incision to diagnose and treat chest diseases. This operation has the advantages of small incision, small injury, and fast recovery and can be widely used in clinics [ 4 ]. Campos and Sharma believed that patients with primary bronchial lung cancer (referred to as lung cancer) and chronic obstructive pulmonary disease (COPD) had common risk factors, such as smoking, so many lung cancer patients were diagnosed with COPD in the preoperative pulmonary function assessment of thoracoscopy [ 3 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Under the direct vision of a high-definition television imaging system, the operation system is inserted into the chest through chest wall incision to diagnose and treat chest diseases. This operation has the advantages of small incision, small injury, and fast recovery and can be widely used in clinics [ 4 ]. Campos and Sharma believed that patients with primary bronchial lung cancer (referred to as lung cancer) and chronic obstructive pulmonary disease (COPD) had common risk factors, such as smoking, so many lung cancer patients were diagnosed with COPD in the preoperative pulmonary function assessment of thoracoscopy [ 3 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Coexisting T2DM and CAD increase complication rates in many but not all studied surgical cohorts. A retrospective cohort study of patients undergoing thoracic surgery for primary tumors found no difference in postoperative complications between patients with and without T2DM 22 . However, the incidence of COPD was not reported in this trial.…”
Section: Discussionmentioning
confidence: 53%